Semiotic Analysis Mineral Water Advertisement 2017 And 2022: Revealing Symbolic Meanings And Cultural Signifiers - Annisa Luluk Firdausie; Santi Agustin (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the semiotic study of mineral drink advertisements version